A prospective study of electrocardiographic and echocardiographic changes in patients with cerebrovascular accidents - Devarapu, Chandrababu; S., Lokesh (International Journal of Advances in Medicine, 2018)
Background: Cerebrovascular accident also called as stroke is defined as the sudden onset of neurological deficit that can be attributable to a focal vascular cause. Many studies in the past have demonstrated the fact that neurological abnormalities produce Electrocardiographic changes without any underlying cardiac lesions. Present study is done to analyze different changes in Electrocardiogram and echocardiographic patterns in the cases of cerebrovascular accidents and to assess whether these different changes have got any prognostic significance in these patients. Methods: In this study 100 patients of acute stroke admitted between May 2011 to August 2012 in Vydehi institute of medical sciences and research centre were considered and subjected to CT scan of brain, Electrocardiogram and 2D echocardiography within 24 hours of admission. Follow-up was done within the hospital to know the prognosis of all the patients. Results: Out of 100 patients majority of them had ischemic stroke accounting for 80% and remaining 20% of patients had haemorrhagic stroke. Abnormal Electrocardiographic changes were seen in 64% patients and 58% patients showed abnormal Echocardiography. ECG changes seen are Tachycardia, QTc prolongation, T wave inversion, ST depression, U waves and Bradycardia. Commonly seen echocardiographic changes were LV dysfunction, mitral valve abnormality, aortic valve abnormality. Overall mortality in patients with abnormal ECG was 28.12% compared to 11.11% in patients with normal ECG and it was statistically not significant. Overall mortality in patients with abnormal 2D echocardiography was 31.03% compared to patients with normal 2D Echocardiography which was 4.76% and it was statistically significant. Conclusions: From this study we conclude that ECG abnormalities in stroke patients do not have any prognostic significance. But LV dysfunction has prognostic significance in predicting mortality in cerebrovascular accident.